The development of an autonomous navigation system with optimal control of an UAV in partly unknown indoor environment. (February 2018) - Mac, Thi Thoa; Copot, Cosmin; Keyser, Robin De; Ionescu, Clara M.
Highlights: An autonomous methodology for a low-cost UAV in partly unknown indoor flight. The development of a position-estimation method using sensor fusion. An optimal controller based on a multi objective particle swarm optimization with an accelerated update methodology. Graphical abstract: Abstract: This paper presents an autonomous methodology for a low-cost commercial AR.Drone 2.0 in partly unknown indoor flight using only on-board visual and internal sensing. Novelty lies in: ( i ) the development of a position-estimation method using sensor fusion in a structured environment. This localization method presents how to get the UAV localization states (position and orientation), through a sensor fusion scheme, dealing with data provided by an optical sensor and an inertial measurement unit (IMU). Such a data fusion scheme takes also in to account the time delay present in the camera signal due to the communication protocols; ( ii ) improved potential field method which is capable of performing obstacle avoiding in an unknown environment and solving the non-reachable goal problem; and ( iii ) the design and implementation of an optimal proportional - integral - derivative (PID) controller based on a novel multi-objective particle swarm optimization with an accelerated update methodology tracking such reference trajectories, thus characterizing a cascade controller. Experimental results validate the effectiveness of the proposed approach.